Utilization of online media as an emergency alternative for implementing community service activities during the COVID-19 pandemic - Syahri Ramadona; Bahrul Ulum; Zulham Effendi; Arbonas Lubis; Slamet Riyadi (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
Community service activities are a routine agenda for every college in Indonesia. although constrained by the pandemic which limits the space for carrying out social activities in the community, it must still be carried out. One solution to overcome the limited space for movement is to carry out community service activities online. By utilizing various kinds of existing social media, community service activities can also run as effectively as activities that go directly to the field. On the one hand, there are indeed many obstacles when interacting with the public through social media, but on the other hand, there is an advantage that is no less important: a much more comprehensive range of locations. Community service activities has been held in Desa Manis, Desa Bangkolak II, Medan Area, Kambu, Desa Atu Kapur, Kadia, Kumpeh Jambi, Manokwari, for two weeks starting on April 19 to May 2, 2021. Starting from the problem of the lack of public interest in studying the Al-Qur'an and familiarizing the recitations of the Al-Qur'an. At this Community service activity, we raised the theme Ramadhan with Al-Qur'an. The Community service activities begin with a village observation process to explore the villages and see the village's potential, which will be the main target in implementing the Community service activities. The programs are designed sequentially starting with discussions between Community service activities groups and lecturers. And it was found that this Community service activities activity would be carried out in two ways, directly and online. The implementation of the Community service activities program is carried out in a balanced manner, starting with planning, implementation, and evaluation at the end of each program. The results achieved from the entire Community service activities program include increased interest in the recitation of the Qur'an for online Community service activities participants and village communities with the holding of recitation presence programs every day. In the social sector, the Islamic book and magazine spread program is one of the programs to introduce and educate rural communities in literacy. Then it was closed with a competition program to increase enthusiasm for Community service activities participants and the community and as an appreciation for their participation in the Community service activities program that we have implemented